ҚАЗАҚСТАНДАҒЫ ТҰРҒЫН ҮЙ САЛАСЫНЫҢ ОРНЫҚТЫ ДАМУЫНЫҢ МЕМЛЕКЕТТІК САЯСАТЫ. (Journal of Economic Research & Business Administration, 2015)
В данной статье рассмотрены основные направления жилищной политики Республики Казахстан. Показанэффективный механизм государственного регулирования жилищного сектора.***This articles describes the main areas of real estate policy of the Republic of Kazakhstan. Showa the effectivemechanism of state regulation of the real estate.